Caracterização e melhoramento de bio-óleo proveniente de semente de goiaba - Psidium guajava L. - Nascimento, Juciara dos Santos (2016)
The present work had as objective to use guava residues (seeds) as biomass for the production of bio-oil through conventional pyrolysis. The biomass presented a moisture content of 3.49 ± 0.03 %, high carbon content (67.04 %), nitrogen (3.96 %), oxygen (22.86 %), hydrogen (6.18 %), protein content (11.81 ± 0.36 %), fiber (11.78 ± 0.45 %), calorific power (24.69 MJ kg -1), ash content (0.76 ± 0.02 %), oil (11.78 ± 0.45 %), cellulose (48.71 %), hemicellulose (11.52 %) and lignin (10.12 %). The thermogravimetric curve of the sample amounts to 90 % of mass loss at 450 °C. The biomass was used in two reactors (quarzto and inox) for the production of bio-oil. Preliminary, the experiments in a quartz reactor evaluated the conditions: temperature (500 to 700 °C), sample mass (5 and 11 g) and pyrolysis time (5 and 10 min) with flow 1mL min-1. The best condition in the quartz reactor was 500 °C, 11 g of seed with the collection time of 5 min and 17.1 % of bio-oil yield. The following experiments were carried out in the steel reactor with constants pyrolysis temperature and flow, 500 ºC and 1mL min-1, respectively. Also, the following variables: sample mass (10 and 20 g), granulometry (seed entire and grain) and salts (K2HPO4 and K3PO4). The best condition in the stainless steel reactor was 20 g of sample, ground seed and without addition of salt, obtaining 23.94 % of bio-oil yield. Since the bio-oil was obtained, it was submitted to liquid-liquid extractions in a 250 mL separating funnel using dichloromethane (DCM) (60 mL) to separate the organic phase (bio-oil) and aqueous phase. For the improvement with model molecule (phenol), diisobutylene was used as reagent and sulfuric acid, Amberlyst (A-15) and sulfated zirconia as catalysts. The conditions for the enhancement were temperature (120 to 180 ° C), molar ratio (1: 1 to 1: 5) and percentage of catalyst (1 to 5% w / w), where the best product conversion was gotten with 150 °C, 1: 3 ratio and 3 % Amberlyst (A-15) yielding 99.8 % product conversion. From the last condition cited above the improvement was made with the bio-oil obtained from the steel reactor. The bio-oils (quartz and steel reactor) were analyzed by infrared, thermogravimetry and GC / MS. After the identification of the compounds by chromatography, the bio-oil from steel reactor (under the conditions: 20 g of sample, ground seed and 10 % K3PO4), showed greater quantity of phenolic compounds being then used in the improvement.